Fully Symbolic TCTL Model Checking for Incomplete Timed Systems - Morbé, Georges; Scholl, Christoph (Electronic Communications of the EASST, 2014)
In this paper we present a fully symbolic TCTL model checking algorithm for incomplete timed systems. Our algorithm is able to prove that a TCTL property is violated or satisfied regardless of the implementation of unknown timed components in the system. For that purpose the algorithm computes over- approximations of sets of states fulfilling a TCTL property φ for at least one implementation of the unknown components and under-approximations of sets of states fulfilling φ for all possible implementations of the unknown components. The algorithm works on a symbolic model for timed systems, called a finite state machine with time (FSMT), and makes use of fully symbolic state set representations containing both the clock values and the state variables. In order to handle incomplete timed systems our model checking algorithm deals with different communication methods between the system and its unknown components, e.g. shared integer variables and urgent and non-urgent synchronization. Our experimental results demonstrate that it is possible to prove interesting properties at early stages of the design when parts of the overall system may not yet be finished. Additionally, fading out components of a large system may dramatically reduce the complexity of the system and thus the effort for verification.